A tool to estimate the contribution of fishing gear modifications to reduce benthic impact. (16th December 2022) - Szostek, Claire Louise; Hiddink, Jan Geert; Sciberras, Marija; Shepperson, Jennifer L.; Thompson, Stephen; Hormbrey, Samantha; Caveen, Alex; Lart, William; Rodmell, Dale; Kaiser, Michel J.
Abstract: The ecological effects of seabed‐penetrating fishing gears depend, in part, on the seabed penetration ( P ) of the gear. We present a gear impact tool that utilizes published data to provide estimated P of globally utilized seabed‐penetrating fishing gears in different sediments and their resulting impact on biological communities. As P correlates with the depletion ( d ) of benthic fauna caused by fishing gears, we use P to calculate d, which can be used to estimate the relative benthic status (RBS; the community biomass of benthic fauna relative to carrying capacity) of the seabed. The tool can provide an objective appraisal of different fisheries management scenarios or interventions (e.g., gear modification, gear substitution, or fishing effort limits) on seabed status, particularly in situations of limited data or resources. For otter trawling in mud, gear modification may provide greater ecological benefits than reducing fishing effort; mean RBS increased by 29% in fished areas by removing the impact from the otter trawl sweeps; this is comparable to reducing fishing effort by approximately 70%. In contrast, modification of beam trawl gear in sand resulted in marginal improvements (6%) in RBS. Modification or removal of gear components with high seabed penetration could result in greater improvements in RBS than spatial management, dependent on gear type and sediment. We provide a quantitative method for estimating the effectiveness of different management scenarios in reducing the benthic impact of seabed‐penetrating fishing gears, enabling an objective evaluation of the trade‐off between spatial management measures (closures or effort reductions) versus technical modifications. This article met the requirements for a Gold‐Gold JIE data openness badge described at http://jie.click/badges